An Analysis of Library Management System Development in South Sulawesi - Ismaya Ismaya; M Yunus Sudirman; Andi Ahmad Chabir Galib; Mawaddatul Maikam (Universitas Pahlawan Tuanku Tambusai, 2023)
Website-based library services have been implemented in various libraries in Indonesia, especially those in South Sulawesi. Almost every librarian employee (librarian) routine is greatly helped by the presence of this technology. This research method was carried out with the aim of conducting a survey of 33 libraries that have implemented a library automation system. While the rest also adopted a similar system. The research method uses qualitative descriptive method through questionnaire surveys and direct visits to several libraries in South Sulawesi. We first do further exploration. The survey results showed that of the 33 libraries that filled out the questionnaire, 24 of them had used the library automation system because of the convenience provided by the use of this technology. The results of the analysis of the data obtained during the research show that the use of the Library Management System in the library fulfills two main aspects of the Technology Acceptance Model (TAM) theory. Utilization of the Library Management System is considered useful to help work in the library, including to assist users in the process of searching for information, the library provides services to users more quickly.